PENGARUH JARAK TANAM PADA METODE LONGLINE TERHADAP PERTUMBUHAN DAN RENDEMEN AGAR Gracilaria verrucosa (Hudson) PAPENFUSS - Ayu Sofiana Desy; Munifatul Izzati; Erma Prihastanti (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2016)
Gracilaria verrucosa is seaweed that is highly potential to be developed. One Factor that can affect on growth G.verrucosa is farming method. The aim of this research is to study the effect distance in longline methods on growth and agar rendement. This research was designed by completely randomized design, which consists of 3 treatments. Each treatment was repeated six times. The treatment were P1 (Planting in distance of 15 cm), P2 (Planting in distance of 25 cm) and P3 (Planting in distance of 35 cm). Parameters measured were biomass, dry weight, absolute and spesfic growth rate and also agar rendement. Resulted data was analysized by analysis of variance with significance level is 5% (P = 0.05). Results showed, that in distance of 15 cm the biomass was 168,73 g, dry weight was 11,89 g, absolute growth rate was 9,81%, spesific growth rate is was 2,3 % and agar rendement was 11.06%. In distance of 25 cm the biomass was 179,91 g, dry weight was 14,85 g, absolute growth rate was 11,43%, specific growth rate was 2,6% and agar rendemen was 11,06%, while in distance of 35 cm the biomass was 167,83 g, dry weight was 13,34 g, absolute growth rate was 9,69%, specific growth rate was 2,21% and agar rendemen was 11%. It can be concluded that in distance of 25 cm resulted in better productivity of Gracilaria verrucosa. Keywords: Gracilaria verrucosa, planting distance, longline, growth, agar rendemen